A new approach to steady state analysis of nonlinear electrical circuits. Issue 3 (2nd May 2017) - Sobczyk, Tadeusz; Radzik, Michał
Abstract : Purpose: The purpose of this study is to identify a novel methodology for direct calculation of steady-state periodic solutions for electrical circuits described by nonlinear differential equations, in the time domain. Design/methodology/approach: An iterative algorithm was created to determine periodic steady-state solutions for circuits with nonlinear elements in a chosen set of time instants. Findings: This study found a novel differential operator for periodic functions and its application in the steady-state analysis. Research limitations/implications: This approach can be extended to the determination of two- or multi-periodic solutions of nonlinear dynamic systems. Practical implications: The complexity of the steady-state analysis can be reduced in comparison with the frequency-domain approach. Originality/value: This study identified novel difference equations for direct steady-state analysis of nonlinear electrical circuits.